Diversity and evolution of entomocorticium (Russulales, peniophoraceae), a genus of bark beetle mutualists derived from free-living, wood rotting peniophora - Araújo, João P. M. (2021)
Symbiosis between insects and fungi arose multiple times during the evolution of both groups, and some of the most biologically diverse and economically important are mutualisms in which the insects cultivate and feed on fungi. Among these are bark beetles, whose ascomycetous cultivars are better known and studied than their frequently-overlooked and poorly understood basidiomycetous partners. In this study, we propose five new species of Entomocorticium, fungal mutualists in the Russulales (Basidiomycota) that are mutualistic symbionts of scolytine beetles. We have isolated these fungi from the beetle mycangia, which are structures adapted for the selective storage and transportation of fungal mutualists. Herein, we present the most complete phylogeny of the closely related genera Entomocorticium and Peniophora and provide insights into how an insect-associated taxon (Entomocorticium) evolved from within a wood-decaying, wind-dispersed lineage (Peniophora). Our results indicate that following a transition from angiosperms to gymnosperms, fungal domestication by beetles facilitated the evolution and diversification of Entomocorticium. We additionally propose four new species: Entomocorticium fibulatum Araújo, Li & Hulcr, sp. nov.; E. belizense Araújo, Li & Hulcr, sp. nov.; E. perryae Araújo, Li & Hulcr, sp. nov.; and E. macrovesiculatum Araújo, Li, Six & Hulcr, sp. nov. Our findings highlight the fact that insect-fungi associations remain an understudied field and that these associations harbor a large reservoir of novel fungal species.